Guaranteed Verification of Dynamic Systems - Schwab, Stefan (Karlsruher Beiträge zur Regelungs- und Steuerungstechnik, 2022)
This work introduces a new specification and verification approach for dynamic systems. The introduced approach is able to provide type II error free results by definition, i.e. there are no hidden faults in the verification result. The approach is based on Kaucher interval arithmetic to enclose the measurement in a bounded error sense. The developed methods are proven mathematically to provide a reliable verification for a wide class of safety critical systems.